Co-development of traumatic stress symptoms and externalising behaviour problems among foster children and the effect of complex trauma: a latent growth curve model - Alina Streicher; Alexander Haselgruber; Katharina Sölva; Brigitte Lueger-Schuster (BMJ Open, 2023)
Objectives Foster children are disproportionately exposed to complex trauma, which may lead to multifaceted impairments that manifest in comorbid emotional and behavioural problems. As little is known about the interactions between comorbid disorders over time, the present study aims to explore the co-development of traumatic stress (TS) symptoms and externalising behaviour problems (EBP), as well as the influence of complex trauma operationalised as cumulative child maltreatment (CM).Setting As part of a 3-year longitudinal study, children from six foster care facilities in Lower Austria were interviewed at three measurement points.Participants Of, in total, 263 participating children, the data of 124 children aged 10–18 years (M=13.5, 28% female) could be analysed.Primary and secondary outcome measures Latent growth curve models were used to examine the co-development of TS symptoms (International Trauma Questionnaire) and EBP (Child Behaviour Checklist) over time; gender, age and cumulative CM (Childhood Trauma Questionnaire) acted as time-invariant covariates.Results While average TS symptoms decreased over time, EBP remained stable. Findings revealed that the initial severity of EBP was both related to the initial severity of TS symptoms and predictive of their rate of change. Cumulative CM was a significant predictor of initial TS symptoms and EBP even after controlling for age and gender, but not for the rates of change.Conclusions Taken together, our results indicate that EBP and TS symptoms are not only cross-sectionally associated but interact with each other over time. Furthermore, an underlying complex trauma could at least partly determine the severity of the two symptom groups. In accordance with a trauma-informed care approach, our study highlights the importance of trauma-specific screening of high-risk children with complex or diffuse symptoms and argues for the benefits of treatments that focus on improving emotion regulation and social skills in addition to addressing trauma.